Proceedings of the 6th International Workshop of Advanced Manufacturing and Automation 2016
DOI: 10.2991/iwama-16.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

A Goal Programming Approach for Green Supply Chain Network Optimization

Abstract: Abstract-Green supply chain management has been focused by both academicians and practitioners in recent years due to the increased public awareness on environmental problems and sustainable development. In this paper, a decision aided model for green supply chain network design and optimization is proposed to justify both economic and environmental performance in an optimal fashion. The model is formulated as a bi-objective goal programming model aiming to balance supply chain cost and CO2 emission, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Coskun et al [15] combined different tax systems and analyzed their impact on the GSCM. Yu et al [16], constructed three green manufacturing decision making models which are penalty and reward model, the non-government intervention model and the tax subsidy model, and discovered that the penalty and reward model is the best model to encourage Supply Chain partners to adopt GSCM practices. Ameknassi et al [17] highlighted that the product recovery and the government subsidy have a positive impact on reverse Supply Chain performance.…”
Section: Literature Review and Related Workmentioning
confidence: 99%
“…Coskun et al [15] combined different tax systems and analyzed their impact on the GSCM. Yu et al [16], constructed three green manufacturing decision making models which are penalty and reward model, the non-government intervention model and the tax subsidy model, and discovered that the penalty and reward model is the best model to encourage Supply Chain partners to adopt GSCM practices. Ameknassi et al [17] highlighted that the product recovery and the government subsidy have a positive impact on reverse Supply Chain performance.…”
Section: Literature Review and Related Workmentioning
confidence: 99%
“…Ilgin and Gupta, [31]. Yu et al, [32] discussed the study of enterprises from sustainability perspective in the Artic regions of the north (especially these organizations which used supply chains) to gain insights into green supply chains. Yu et al, [32] investigated as a case study in the North Artic regions, the development of green supply chains and preservation of the organizations which adopted it.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al, [32] discussed the study of enterprises from sustainability perspective in the Artic regions of the north (especially these organizations which used supply chains) to gain insights into green supply chains. Yu et al, [32] investigated as a case study in the North Artic regions, the development of green supply chains and preservation of the organizations which adopted it. Amalnick and Saffar, [33] developed network of supply chains by considering the ambiguity involving effects of environment while focusing on decision variables minimizing environmental and economic costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coskun et al [16] combined different tax systems and incentive subsidy policies, and analyzed their impacts on GSC and green manufacturing. Yu et al [17] constructed three green manufacturing decision-making models under uncertain demand, namely, the reward and penalty mechanism model, the non-government intervention model, and the tax-subsidy mechanism model, and discovered that the reward and penalty mechanism is the best model to incentivize supply chain members to recycle and remanufacture waste products. Ameknassi et al [6] suggested that the performance of the reverse supply chain can be effectively improved by elevating the price of product recovery and government subsidy, and established a model to optimize the government subsidy and product recovery price for reverse supply chain.…”
Section: Introductionmentioning
confidence: 99%